Annie Bleile-Kratzer's 1st Birthday Party - Watkins, Howard::::::::: (1983)
Nancy Bleile holding summer outfit present, Devon Bleile-Kratzer, ?, Annie Bleile-Kratzer, Art Wille, ? Annie holding pink doll and wearing red shoes